Clinical Efficacy of Arthroscopic Partial Wrist Arthrodesis: Comparative Analysis Across Wrist Pathologies and Fusion Techniques - Chen, Jian-Jiun; Liou, Jia-You; Lo, I-Ning; Yin, Cheng-Yu; Wang, Jung-Pan; Huang, Yi-Chao (Journal of Wrist Surgery, 2025)
This study evaluated clinical and functional outcomes of arthroscopic partial wrist arthrodesis for various wrist pathologies, including Kienböck's disease, radiolunate (RL) arthritis, and scaphoid nonunion advanced collapse (SNAC) or scapholunate advanced collapse (SLAC), comparing different fusion techniques.We retrospectively analyzed 26 patients treated by a single surgeon between October 2015 and November 2023. Procedures included scaphocapitate (SC) fusion for Kienböck's disease, RL fusion for RL arthritis, lunatocapitate (LC), or four-corner fusion (4CF) for SNAC/SLAC. Primary outcomes assessed were fusion rate, reoperation rate, wrist range of motion (ROM), Visual Analog Scale pain scores, QuickDASH, and modified Mayo wrist scores.Solid fusion was achieved in 100% of SC fusion and 4CF groups but was lower in RL (67%) and LC (43%) fusion groups. LC fusion had the highest reoperation rate (57%). Postoperatively, significant pain relief occurred across all groups. The LC group demonstrated notable ROM reduction (median from 100-degree preoperative to 70-degree postoperative, p = 0.002), higher QuickDASH scores (median 25.5), and lower Mayo scores (median 60). Conversely, minimal ROM loss and superior functional outcomes were observed in SC fusion, RL fusion, and 4CF groups. Patient satisfaction scores remained consistently high (7.5–10).Arthroscopic partial wrist arthrodesis provides favorable outcomes, particularly in SC and 4CF procedures, with higher fusion rates, better motion preservation, and quicker healing compared with traditional open techniques. However, LC fusion is associated with higher complications and reduced functional outcomes, emphasizing the importance of careful patient selection and surgical planning.
Keywords: wrist; carpal bone; osteoarthritis; arthroscopy; arthrodesis; fusion